Development of automated waste separator to improve organic fertilizer production efficiency in Srunggo II village, Bantul - Widodo Aris Slamet; Widyasmoro Widyasmoro; Kwong Henry; Fazni Wan Nur; Kinasih Raden Safinatul Aula Wiji; Suparmono Suparmono; Abidin Mohd Abidzar Zainol; Bin Shahul Hamid Mohamed Nazreen (BIO Web of Conferences)
The National Zakat Amil Agency (BAZNAS) provided support in the form of a Compost House from PT. Ansaf to the Berkah Cerme Livestock Group on September, 2023. Through the compost house, livestock owners can establish new sustainable businesses by generating organic fertilizer from their livestock waste. However, the Livestock Group encounters a challenge in the production process, particularly in the separation of animal waste from gravel and rapen. The manual management of manure sorting is deemed inefficient due to its time-consuming nature. Additionally, the imbalance between livestock numbers and available labor, also results in the accumulation of manure, which could threaten livestock health. Findings from the need assessment indicated a requirement for technological tools that can enhance the efficiency of livestock farmers while preserving the health of cattle throughout the organic fertilizer processing. Through collaboration with Singapore Polytechnic, Universitas Muhammadiyah Yogyakarta team able to realize this and develop an Automated Waste Separator tool. The approach included counselling programs, prototype and tool development, training, and mentoring. The result was the Automated Waste Separator, which has proven to enhance the efficiency of farmers in separating animal waste. The socialization and training sessions have made farmers more skilled in using the AWS tool.